Co‐design of the DELIGHT (Dementia Lifestyle Interventions for Growing Healthy Together) program for persons living with dementia and care partners. (December 2021) - Middleton, Laura E; Keller, Heather; McAiney, Carrie A; Bechard, Lauren Elizabeth; Wei, Cindy; Koch, Melissa; Heibein, William; Roth, Gail; Schneider, Lloyd; Shoemaker, David; Shoemaker, Margaret; ,
Abstract: Background: Persons living with dementia (PLWD) and family care partners (CPs) want to improve their health, maintain independence, and enhance well‐being. Multi‐domain interventions towards this goal are needed, but few are available and fewer were co‐created with PLWD, CPs, and program providers. The objective of the DELIGHT project is to use a participatory approach to co‐design a feasible, effective multi‐domain intervention (the DELIGHT program) that meets the health and well‐being goals of PLWD and CPs. Method: Using a participatory approach, the DELIGHT project is guided by a core team of researchers, PLWD, CPs, and an Alzheimer Society representative. The co‐design team included the core team and additional PLWD/CPs, exercise professionals, dietitians, health care professionals, and community service providers (n=29). Due to COVID‐19, research team meetings have been virtual since May 2020. The co‐design was planned for four in‐person, half‐day sessions but was transitioned to six online, 1.5‐hour sessions, using small breakout rooms for discussion. The co‐design meetings focused on identifying target population, key outcomes of the program and developing program components and structure. During co‐design meetings, two or three guiding questions were set to focus discussion on a specific topic (e.g., exercise). The final co‐design session focused on the overall structure of the DELIGHT program. The core team then reflected on co‐design discussions and decisions and made final decisions on program structure. Program resources were iteratively designed with the core team, co‐design team, and other external stakeholders (including an illustrator). Result: The DELIGHT program is designed to promote well‐being among PLWD and CP. Engagement soon after diagnosis is a goal. The program will meet twice per week for one hour of exercise and thirty minutes of facilitated discussion/education with a healthy snack and social engagement. Education will focus on healthy eating, sleeping well, mental well‐being, social connection, and physical activity. Program resources and manual are in development. Conclusion: The DELIGHT program was co‐created by PLWD, CPs, researchers, and community stakeholders to meet the health and well‐being goals of PLWD and CPs. The on‐line and in‐person program options will be piloted and evaluated in fall 2021.